Conventional and three-dimensional photography as a tool to map distribution patterns of in-transit melanoma metastases on the lower extremity - Müller, Kilian; Berking, Carola; Voskens, Caroline; Heppt, Markus; Heinzerling, Lucie; Koch, Elias; Kramer, Rafaela; Merkel, Susanne; Schuler-Thurner, Beatrice; Schellerer, Vera; Steeb, Theresa; Wessely, Anja; et al. (Frontiers in Medicine, 2023)
Background: In melanoma, in-transit metastases characteristically occur at the lower extremity along lymphatic vessels. Objectives: The objective of this study was to evaluate conventional or three-dimensional photography as a tool to analyze in-transit metastasis pattern of melanoma of the lower extremity. In addition, we assessed risk factors for the development of in-transit metastases in cutaneous melanoma. Methods: In this retrospective, monocentric study first we compared the clinical data of all evaluable patients with in-transit metastases of melanoma on the lower extremity (n = 94) with melanoma patients without recurrence of disease (n = 288). In addition, based on conventional (n = 24) and three-dimensional photography (n = 22), we defined the specific distribution patterns of the in-transit metastases on the lower extremity. Results: Using a multivariate analysis we identified nodular melanoma, tumor thickness, and ulceration as independent risk factors to develop in-transit metastases ITM (n = 94). In patients with melanoma on the lower leg (n = 31), in-transit metastases preferentially developed along anatomically predefined lymphatic pathways. In contrast when analyzing in-transit metastases of melanoma on the foot (n = 15) no clear pattern could be visualized. In addition, no difference in distance between in-transit metastases and primary melanoma on the foot compared to the lower leg was observed using three-dimensional photography (n = 22). Conclusion: A risk-adapted follow-up of melanoma patients to detect in-transit metastases can be applied by knowledge of the specific lymphatic drainage of the lower extremity. Our current analysis suggests a more complex lymphatic drainage of the foot.
CRIS-Team Scopus Importer:2023-02-10
Keywords: 3D photography; in-transit metastasis; lower extremity; lymphatic pathways; melanoma